Ovarian Leydig Cell Hyperplasia: An Unusual Case of Virilization in a Postmenopausal Woman - Jaya M. Mehta; Jeffrey L. Miller; Anthony J. Cannon; Stacey K. Mardekian; Lawrence C. Kenyon; Serge A. Jabbour (Case Reports in Endocrinology)
Objective. To report an unusual case of ovarian Leydig cell hyperplasia resulting in virilization in a postmenopausal woman. Methods. Patient’s medical history and pertinent literature were reviewed. Results. A 64-year-old woman presented with virilization with worsening hirsutism, deepening of her voice, male musculature, and male pattern alopecia. Her pertinent past medical history included type 1 diabetes, hyperlipidemia, and hypertension. Her pertinent past surgical history included hysterectomy due to fibroids. On further work-up, her serum total testosterone was 506 ng/dL (nl range: 2–45) and free testosterone was 40 pg/mL (nl range: 0.1–6.4). After ruling out adrenal causes, the patient underwent an empiric bilateral oophorectomy that showed Leydig cell hyperplasia on pathology. Six weeks postoperatively, serum testosterone was undetectable with significant clinical improvement. Conclusion. Postmenopausal hyperandrogenism can be the result of numerous etiologies ranging from normal physiologic changes to ovarian or rarely adrenal tumors. Our patient was found to have Leydig cell hyperplasia of her ovaries, a rarely reported cause of virilization.